Characterisation of the effects of age and body mass index on the ultrasound carotid artery wall using RF time series. Issue 2 (3rd March 2020) - Sharifi, Samrand; Behnam, Hamid; Alizadehsani, Zahra
ABSTRACT: Carotid atherosclerosis and brain strokes are mainly due to plaques and artery wall stiffness, therefore, novel methods are required to investigate such diseases at initial stages. Many Studies, using radiofrequency signals, have indicated changes in artery wall due to ageing and body mass index in healthy people. In this study, a novel method that uses power spectrum and Nakagami distribution methods based on radiofrequency signals evaluates changes of acoustic and statistical features of carotid artery wall. The posterior wall (intima-media) was extracted for 31 healthy participants including 19 men and 12 women (with age distribution of 37.54 ± 14.89 ) using their radiofrequency signals. The results showed that the power spectrum parameters correlate with age. The quantitative analysis indicated that power spectrum parameters decrease along frames by age. In addition, scaling and Nakagami parameters showed significant correlations with age ( r = 0.813, p < 0.0001 ; r = 0.482, p < 0.0001 ) and body mass index ( r = 0.678, p < 0.0001 ; r = 0.337, p < 0.01 ) respectively. Nakagami distribution parameters increase by age and are higher in overweight participants. However, there were no significant correlations between these features and systolic/diastolic blood pressure and sex. Our Results raise hopes that the proposed method may be effective in diagnosing of atherosclerosis.